The solution is simple
y= x^(1/lnx)
now take the ln of both sides
lny = ln[x^(1/lnx)]
This becomes
lny = (1/lnx)*(lnx)
because ln(a^b) = b*lna
So lny = 1
now take the exponent of both sides
y = e, which is a constant
dy/dx = 0
2007-01-10 15:36:41
·
answer #1
·
answered by The Answerer 3
·
0⤊
0⤋
Take ln of both sides.
ln y = ln x ^ 1/lnx
ln y = 1/ln x (ln x) bring exponent down
ln y = 1 cancellation
y = e
y' = 0.
2007-01-10 15:37:53
·
answer #2
·
answered by math_ninja 3
·
1⤊
0⤋
e^(6) is purely a variety (approx 403, do it on your calculator). so which you will think of of the question as being something like: e^(7x) - 403 The by-manufactured from a variety is 0, as a result the by-manufactured from the question is: 7e^(7x) i'm a severe college maths instructor and the respond is 7e^(7x) you're precise: the rule of thumb of derivitives is that der.e^x=e^x. notwithstanding, it is purely for e^x. listed right here are some examples of derivatives e^2x ? 2e^2x e^x² ? 2xe^x² e^(x² - 3x) ? (2x -3)e^(x² - 3x) so which you ought to multiply e with tips from the differential of the flexibility.
2016-10-06 23:40:15
·
answer #3
·
answered by kinjorski 4
·
0⤊
0⤋
y = x^(1/lnx) ----(i)
=> let us put lnx = t
=> x = e^t
substituting these values in equation (i)
=> y = e^t(1/t)
=> y = e (cuz t X 1/t = 1)
Differentiating above equation, we get
=> dy/dt = 0
2007-01-10 15:39:53
·
answer #4
·
answered by rishi 2
·
0⤊
0⤋
take ln on both sides of equation. you get
lny=ln(x^(1/lnx))=(1/lnx)*lnx=1
therefore
lny=1
taking derivative,
d(lny)/dx=0
or, 1/y * dy/dx = 0
since y not equal to 0, dy/dx = 0
2007-01-10 15:38:30
·
answer #5
·
answered by catfan 1
·
0⤊
0⤋
take ln on both sides
lny=1*lnx/lnx
lny=1
differentiate now
(1/y)*dy/dx=0
dy/dx=0
2007-01-10 15:37:54
·
answer #6
·
answered by IN PURSUIT OF WISDOM 2
·
0⤊
0⤋
You have to use a differentiation technique called "logarithmic differention." Basically, you take the natural logarithm of both sides of the equation and then use implicit differention. It is important to know that the derivative of ln(x) is 1/x:
y = x^(1/ln(x))
ln(y) = ln(x)^(1/ln(x)) [took natural log of both sides]
ln(y) = (1/ln(x))ln(x) [simplified using laws of logarithms*]
ln(y) = 1 [simplified]
(1/y)(dy/dx) = 0 [differentiatedd]
(dy/dx) = 0
*ln(A)^B = B(ln(A)) (property of logarithms)
Good luck.
2007-01-10 15:43:42
·
answer #7
·
answered by student2000 2
·
0⤊
0⤋
let e^z = x^(1/lnx)
z = (1/lnx)lnx = 1
d/dx(x^(1/lnx) = d/dx(e^1) = 0
2007-01-10 15:55:12
·
answer #8
·
answered by Helmut 7
·
0⤊
0⤋